Nonlinear optics on nano/micro-hierarchical structures on metals: focus on symmetric and plasmonic effects. (1st January 2017) - Ogata, Yoichi; Guo, Chunlei
ABSTRACT: In this review, the authors study their creation of nano/micro-hierarchical structures on Ag and Ni substrates by femtosecond laser treatment and their investigation of their optical second-harmonic generation (SHG) signal intensities by SHG spectroscopy. The authors obtained the nanostructure-covered microgroove and microcube structures. These hierarchical surface structures were found to modify significantly the optical nonlinearity of the metal surfaces. The macroscopic symmetry of the surface's shapes influenced SHG, and the excitation of surface plasmons enhanced SHG. On the other hand, the nanostructures on the microstructures had an additional effect on the generated SHG. For the microcube structures, the additional SHG emission was suppressed by removing a large amount of nanostructures. Left SHG was discussed by the effect of the propagating delay.